Podejście zadaniowe (enfoque por tareas) a strategie komunikacyjne w nauczaniu języka hiszpańskiego jako obcego - Spychała, Małgorzata (Neofilolog, 2019)
The article discusses task-based learning (TBL) in Spanish: enfoque por tareas, which is a teaching approach whose aim is to develop the learner’s communicative competence as well as to help the teacher activate language learners in the classroom – in this case learners of Spanish. The article describes the main objectives of the task and projects defined in the Common European Framework, including the proposed activities designed to fulfill a given task. The final section presents a sample set of lessons following TBL and analyzes the advantages and disadvantages of this approach.